Salvia miltiorrhiza polysaccharide activated macrophages and improved the disease resistance of sturgeon against Aeromonas hydrophila. Issue 127 (August 2022) - Chen, Daiyu; Yang, Lei; Yang, Fei; Pei, Qiaolin; Lu, Lu; Huang, Xiaoli; Ouyang, Ping; Geng, Yi; Li, Zhiqiong; Zhang, Xin; Wang, Jun; Chen, Defang
Abstract: The use of plant polysaccharides in aquaculture is recognized as a healthy strategy to enhance disease resistance and reduce medication use. Salvia miltiorrhiza polysaccharide (SMP) can regulate the immune function of higher vertebrates. However, the effects of SMP on fish have not been fully investigated. In this study, the ability of SMP to activate the macrophages of Siberian sturgeon ( Acipenser bareii ) was analyzed in vitro . The effects of SMP on immune cell activity of hybrid sturgeon ( A. baerii ♀ × Acipenser schrenckii ♂) and resistance to Aeromonas hydrophila were further detected in vivo . The in vitro results showed that SMP up-regulated phagocytosis, respiratory burst, inducible nitric oxide synthase activity, nitric oxide (NO) concentration, and cytokine mRNA expression of macrophages. The in vivo results showed that dietary supplementation with SMP enhanced the respiratory burst of macrophages and proliferative activity of lymphocytes. Dietary supplementation with SMP increased serum concentrations of lysozyme and NO, and improved the survival rate of hybrid sturgeon challenged with A. hydrophila. Collectively, these results suggest that SMP can improve the immune function and disease resistance of sturgeon. This study provides a theoretical basis for the application of SMP for healthy farming of sturgeon. Highlights: Salvia miltiorrhiza polysaccharide (SMP) activated macrophages of sturgeon i n vitro. SMP improved the immune cell activity of sturgeon in vivo. SMP enhanced the disease resistance against Aeromonas hydrophila in sturgeon. SMP alleviated pathological damage to the spleen, liver, and valvular intestine of sturgeon post-challenge with A. hydrophila.